CZTS based solar cells: design & performance analysis - Rahaman, Md. Mamunur; Chowdhury, Arbab; Waky, Syed Irshan (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.